Adaptive Transceiver Architecture With QoS Provision for OCDMA Network Based on Logic Gates - Hassan Yousif Ahmed (IEEE, 2021)
Utilization of an adaptable transceiver with quality of service (QoS) features is a promising notion to build next generation optical network. This paper proposes an adaptive transceiver design by adopting logic gates in the optical domain. The proposed design offers multiple scenarios to support QoS diversity with a slight modification of conventional optical code division multiple access (OCDMA) transceiver architecture through Sigma Shift Matrix (SSM) signature code. In particular, the proposed transceiver design categorizes the users into two classes of service, one having a higher quality level and the other having a lower quality level. Users of high class transmit at low interference versus high interference power for low classes’ users. To switch between the multiple scenarios, an optical Mux performs digital operation is developed and integrated to the transceiver design. This type of MUX is built by using a semiconductor optical amplifier (SOA). In addition, a comprehensive algorithm is developed to control the function of the adaptable transceiver. Five scenarios were formed and investigated to offer a platform for a different type of applications. A proof concept using Optisystem software demonstrates ability of the proposed architecture to efficiently switch between different levels of QoS as per user requirement and provide desired transmission capacity